Looking for Mature Faith in the Missions of Religiously Affiliated Institutions of Higher Education. Issue 3 (27th May 2017) - Weeks, Matthew; Winningham, Katie James; Winningham, Brandon
ABSTRACT: In this study, we investigated Benson, Donahue, and Erikson's (1993) concept of faith maturity as expressed by institutions of higher education (IHE) claiming religious affiliation. We examined the institutional mission statements of 87 schools affiliated with six Protestant denominations in search of evidence of their intention to develop the Vertical (V) and Horizontal (H) dimensions of faith maturity (Benson, Donahue, & Erikson, 1993). Contrary to this conceptualization of a mature faith, expressions of V and H dimensions were negatively correlated. There was considerable variability in the expression of both V and H dimensions, with Southern Baptist institutions being highest in the V dimension, and United Church of Christ and Lutheran institutions being highest in the H dimension. Although expression of V and H characteristics did not match Benson et al.'s definition of a mature faith, there was some evidence these dimensions corresponded with institutional practices related to relevant student experiences. Overall, the H dimension was emphasized in the mission statements more than the V dimension. These findings have implications for reviewing institutional practices regarding student curricular and co-curricular experiences.